Factor proportions, technology and West German industry's international trade patterns: Worldwide and regional - Frank Wolter (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1976)
Among the hypotheses which have been advanced to explain a country's international trade patterns the neo-factor proportions hypothesis and, more recently, the neo-technology hypothesis have exerted particular appeal both in theory and in empirical testing. The former introduces intercountry differences in human capital endowment and interindutry differences in human capital requirements as decisive determinants of international specialization into the framework of a Heckscher-Ohlin world; the latter stresses intercountry differences in the capability to innovate and interindustry differences in susceptibility to innovations as the major force governing structure and change of a country's comparative advantage. Although formulated as two separate hypotheses, the difference between them is not immediately obvious. The main difficulty in differentiating stems from the comprehensive character of the human capital concept, as such surely encompassing innovativeness, the key variable of the neo-technology hypotheses. Yet this very comprehensiveness means that characteristics other than innovativeness can also account for human capital. Put differently, human capital is a necessary but not a sufficient condition for innovativeness, both across countries and across industries. Further, innovativeness differs from other possible components of human capital in that in leads to intercountry differences in production technology - a determinant of trade flows explicitely ruled out by the neo-factor proportions hypothesis.
Keywords: 330